2007
DOI: 10.1111/j.1872-034x.2007.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum measures of iron status and HFE gene mutations in patients with hepatitis B virus infection

Abstract: Aim:  We tested associations between HFE mutations and hepatitis B virus (HBV) infection. We also explored measures of total body iron status and their association with chronic HBV infection. Methods:  Serum measures of iron status and HFE mutations (C282Y, H63D, and S65C) were assessed in 344 Iranian patients with chronic HBV infection (214 asymptomatic carriers, 130 patients with chronic progressive liver disease [CPLD]) and 302 controls. Results:  Frequencies of HFE mutations did not differ between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
6
13
0
Order By: Relevance
“…Overall, these results were compatible to studies by Thorburn et al [2002] and Sendi et al [2005]. However, several reports showed previously a significant difference in serum ferritin between patients with chronic Hepatitis B and C and healthy controls [Lebray et al, 2004;Ghaziani et al, 2007]. Patients with elevated serum iron markers were more commonly male, drank more alcohol, and had more active chronic hepatitis with increased liver fibrosis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, these results were compatible to studies by Thorburn et al [2002] and Sendi et al [2005]. However, several reports showed previously a significant difference in serum ferritin between patients with chronic Hepatitis B and C and healthy controls [Lebray et al, 2004;Ghaziani et al, 2007]. Patients with elevated serum iron markers were more commonly male, drank more alcohol, and had more active chronic hepatitis with increased liver fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the homozygous C282Y status was absent from individuals with chronic hepatitis as well as controls. Overall, these findings are in agreement with well documented studies from the Middle-East and eastern-Asia [Mah et al, 2005;Ghaziani et al, 2007] but differ from the report of Sendi et al [2005] showing that in Iranians patients, the frequency of major mutation C282Y in HFE gene with HBV infection is higher than control subjects (4% vs. 0%, P ¼ 0.02). However, it must be stressed that the latter study was performed on a limited number of patients (n ¼ 75).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, high levels of serum ferritin and transferrin have been reported in these patients (13,33), although the causes of the increased serum ferritin and transferrin saturation remain unclear. Our observation that LHBsAg inhibited transferrin uptake by human hepatocytes provides a clue to the cause of the disordered metabolism of iron ions.…”
Section: Discussionmentioning
confidence: 99%
“…They found a high prevalence (> 15%) of C282Y-mutant genotypes (CY and YY) in both groups of Iranian patients with hepatitis C as well as healthy individuals. In previous studies from Iran, the mutant genotypes of this polymorphism was rarely observed in healthy Iranian individuals (4,5) and even in Iranian patients with liver diseases and HH (5-7). While the data presented by Gerayli et al (1) regarding the high prevalence of C282Y-mutant genotypes in northeast Iran can be of great interest it should however be noted that this high prevalence of mutant-C282Y genotypes can be a result of genotyping error.…”
mentioning
confidence: 85%